A meta-analysis examining technology-assisted L2 vocabulary learning. Issue 2 (27th May 2022) - Yu, Aiqing; Trainin, Guy
Abstract: This meta-analysis examines the effectiveness of technology-assisted second language (L2) vocabulary learning as well as identifies factors that may play a role in their effectiveness. We found 34 studies with 2, 511 participants yielding 49 separate effect sizes. Following the procedure developed by Hunter and Schmidt (2004 ), we corrected for sample size bias and measurement error. The overall effect size for using technology to learn L2 vocabulary was d = 0.64, which is a moderate effect size. The Q statistic indicated a significant variability in effect size, so we followed up with a theory-driven moderator analysis. The results of the moderator analysis revealed that learners benefited more from technology-assisted L2 vocabulary learning with incidental instruction than with intentional instruction; types of assessment were not significant moderators of the effect on technology-assisted L2 vocabulary learning; technology-assisted L2 vocabulary learning is more effective when the target language is close to the learner's first language; college students benefited more from technology-assisted L2 vocabulary learning than K–12 students; and, finally, mobile-assisted L2 vocabulary learning was more effective than computer-assisted L2 vocabulary learning.